Frailty transitions and risk of chronic kidney disease: insights from the China Health and Retirement Longitudinal Study - Xiaotong Sun; Che Wang; Rujie Zheng; Zhihao Liu; Wenjuan Song; Xiaoyu Du; Chunlei Liu; Chengzhi Lu (Renal Failure)
Background Frailty is increasingly recognized as a critical factor in the risk of chronic kidney disease (CKD), and it is also a condition that can undergo transitions. However, the relationship between frailty transitions and CKD risk in aging populations remains underexplored. This study aims to investigate the association between frailty transitions and CKD risk in middle-aged and older adults using data from the China Health and Retirement Longitudinal Study.Methods Frailty was assessed using a 40-item Frailty Index (FI), with participants categorized into three groups: robust (FI ≤ 0.10), pre-frail (0.10 < FI ≤ 0.21), and frail (FI > 0.21). Frailty transitions were tracked between the first and second waves of the study. Data on CKD incidence were obtained from self-reported physician-diagnosed kidney disease. Cox proportional hazards models were employed to evaluate the risk of CKD, with adjustments made for potential confounders.Results Among 12,050 participants (52.60% female, mean age 58.37), those who progressed to frailty or pre-frailty had an increased risk of CKD compared with stable participants (HR 1.74, p < 0.001). In contrast, individuals who recovered from frailty to robust or pre-frail status had a reduced CKD risk (HR 0.71, p = 0.023). The results of the sensitivity analysis, which showed consistent findings, support the reliability of the results.Conclusion Frailty transitions are significantly associated with the risk of CKD. Worsening frailty is linked to an increased risk of CKD, while improvement in frailty is associated with a lower risk of CKD.